Protection Duration of COVID-19 Vaccines: Waning Effectiveness and Future Perspective - Zhuang, Chunlan; Liu, Xiaohui; Chen, Qi; Sun, Yuxin; Su, Yingying; Huang, Shoujie; Wu, Ting; Xia, Ningshao (Frontiers in Microbiology, 2022)
The COVID-19 vaccines have very successfully decreased the disease risk as we know, some key information remains unknown due to the short development history and the lack of long-term follow-up studies in vaccinated populations. One of the unanswered issues is the protection duration conferred after COVID-19 vaccination, which appears to play a pivotal role in the future impact of pathogens and is critical to inform the public health response and policy decisions. Here, we review current information on long term effectiveness of different COVID-19 vaccines, persistence of immunogenicity, and gaps in knowledge. Meanwhile, we also discuss the influencing factors and future study prospects on this topic.